Right to Health Care for Refugees from Ukraine - Zieliński, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Approximately 9.2 million displaced persons from Ukraine, mostly women and children, have crossed the Polish-Ukrainian border since the war began. The situation calls for continuous legislative efforts to regulate the legal situation of those fleeing the war, as numerous difficulties are faced by Ukrainian citizens arriving in Poland, medical entities and medical professionals The Polish parliament quickly passed the provisions of the law of March 12, 2022 on assistance to Ukrainian citizens in connection with the armed conflict on the territory of that country. The subject of this article is the legal analysis of the regulations of this law in the field of medical care for Ukrainian citizens residing in Poland. In addition, the purpose of the publication is to propose a proper interpretation of the provisions guaranteeing health care for new residents of Poland. The Polish parliament quickly passed the provisions of the law of March 12, 2022 on assistance to Ukrainian citizens in connection with the armed conflict on the territory of that country. The subject of this article is the legal analysis of the regulations of this law in the field of medical care for Ukrainian citizens residing in Poland. In addition, the purpose of the publication is to propose a proper interpretation of the provisions guaranteeing health care for new residents of Poland, in accordance with the intention of the legislator of this act.